PENGARUH PENGGUNAAN METODE PEMBELAJARAN GIVING QUESTION AND GETTING ANSWER TERHADAP MOTIVASI BELAJAR PPKn SISWA KELAS VII MTs NEGERI 1 INDRAGIRI HULU - Apriandi Arifwan; Gimin Gimin; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of using Giving Question and Getting Answer learning method toward social students motivation in learning PPKn at MTs Negeri 1 Indragiri Hulu. This study aims to determine the effect of of using Giving Question and Getting Answer learning method toward students’ motivation in learning PPKn at MTs Negeri 1 Indragiri Hulu.This research was a quantitative descriptive study that was experimental. Population in this study were social students of class VII MTs Negeri 1 Indragiri Hulu. The sample in this research was taken based on